2019
DOI: 10.1590/1980-5373-mr-2019-0321
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Thermal Stability of Faujasite Zeolite Synthesized from Kaolin Waste from the Amazon

Abstract: The waste from the processing of kaolin in the Amazonian region of Brazil was subjected to a calcination process at 700°C for 2 h to obtain metakaolin, which, together with sodium hydroxide and sodium silicate, formed the reaction mixture. This mixture was subjected to an aging step (24 h at 60 rpm), and a subsequent hydrothermal process at 110°C for 10 h. By means of X-ray diffraction (XRD), differential thermal and thermogravimetric analysis (DTA/TG) and scanning electron microscopy (SEM) techniques, the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As a consequence of this process, a large amount of waste is generated, estimated at around 80% to 90% of the total volume of the exploited mineral [128]. This fact has prompted various investigations focused on the recovery of waste originating from the extraction of kaolin as a raw material in the manufacture of zeolites [129,130], molecular sieves [131] or cordierite [132]. The studies focused on the valorization of kaolin processing wastes in the manufacture of mullite-based ceramics are summarized below.…”
Section: Kaolin Processing Wastementioning
confidence: 99%
“…As a consequence of this process, a large amount of waste is generated, estimated at around 80% to 90% of the total volume of the exploited mineral [128]. This fact has prompted various investigations focused on the recovery of waste originating from the extraction of kaolin as a raw material in the manufacture of zeolites [129,130], molecular sieves [131] or cordierite [132]. The studies focused on the valorization of kaolin processing wastes in the manufacture of mullite-based ceramics are summarized below.…”
Section: Kaolin Processing Wastementioning
confidence: 99%
“…The conversion to the corresponding oxide was made by multiplying the element concentration with 1.8895 (Al 2 O 3 ), 1.4297 (Fe 2 O 3 ), 1.3392 (CaO), 1.6583 (MgO), 1.2046 (K 2 O), 1.3480 (Na 2 O), 1.2912 (MnO), and 1.6683 (TiO 2 ) [29]. The SiO 2 and loss of ignition (LOI) were determined by gravimetry [38]. A potash feldspar (BCS-CRM 376/1) certified reference material (Bureau of Analyzed Samples, Middlesbrough, UK) with a similar matrix to zeolite samples was analyzed for quality control purposes.…”
Section: Characterizationmentioning
confidence: 99%
“…In the case of nepheline, its production from natural zeolites waste or from zeolites synthesized from waste appears to be one of the most promising routes. In this way, Han et al 13 reported on the manufacture of nepheline porous ceramics, with improved strength and well thermal insulation performance, from waste zeolite powders, while de Castro et al 14 described its production from fajausite prepared from kaolin waste.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, Han et al 13 . reported on the manufacture of nepheline porous ceramics, with improved strength and well thermal insulation performance, from waste zeolite powders, while de Castro et al 14 . described its production from fajausite prepared from kaolin waste.…”
Section: Introductionmentioning
confidence: 99%